An Unprecedented Stimuli‐Controlled Single‐Crystal Reversible Phase Transition of a Metal–Organic Framework and Its Application to a Novel Method of Guest Encapsulation. Issue 29 (30th May 2018) - Tan, Fangchang; López‐Periago, Ana; Light, Mark E.; Cirera, Jordi; Ruiz, Eliseo; Borrás, Alejandro; Teixidor, Francesc; Viñas, Clara; Domingo, Concepción; Planas, José Giner
Abstract: The flexibility and unexpected dynamic behavior of a third‐generation metal–organic framework are described for the first time. The synthetic strategy is based on the flexibility and spherical shape of dipyridyl‐based carborane linkers that act as pillars between rigid Co/BTB (BTB: 1, 3, 5‐benzenetricarboxylate) layers, providing a 3D porous structure (1 ). A phase transition of the solid can be induced to generate a new, nonporous 2D structure (2 ) without any loss of the carborane linkers. The structural transformation is visualized by snapshots of the multistep single‐crystal‐to‐single‐crystal transformation by single‐crystal and powder X‐ray diffraction. Poor hydrogen bond acceptors such as MeOH, CHCl3 or supercritical CO2 induce such a 3D to 2D transformation. Remarkably, the transformation is reversible and the 2D phase2 is further converted back into1 by heating in dimethylformamide. The energy requirements involved in such processes are investigated using periodic density functional theory calculations. As a proof of concept for potential applications, encapsulation of C60 is achieved by trapping this molecule during the reversible 2D to 3D phase transition, whereas no adsorption is observed by straight solvent diffusion into the pores of the 3D phase. Abstract : Metal–organic frameworks (also known as porous coordination polymers) can exhibit a reversible porous 3D (1 ) to nonporous 2D (2 ) phase transition by metal–nitrogen bond breaking and re‐forming without the loss of the critical carborane‐based linkers. The structural transformation can be used for entrapping molecular guests that are too large to diffuse into the initial 3D structure.